Towards Climate Resilience of the Built Environment: A GIS-Based Framework for the Assessment of Climate-Proof Design Solutions for Buildings - Valeria D’Ambrosio; Ferdinando Di Martino; Enza Tersigni (Buildings, 2023)
Countering climate impacts by increasing resilience is a pivotal issue in scientific debate, in which the awareness of the risks of extreme weather phenomena is growing. Cities have been revealed to be increasingly unsuited to the changing climate and vulnerable to it due to their settlement patterns, constructive practices and living habits. Scientifically addressing the issue of climate-proof design requires the development of knowledge models and processes capable of managing the complexity of information needed to guide the transformation of the built environment. In this paper, a model for assessing climate resilience scenarios for the heatwave phenomenon is proposed by implementing a database of technical climate-proof solutions for climate adaptation and mitigation aimed at increasing the indoor comfort and reducing the CO2 emissions of buildings. The model is implemented through a GIS-based framework and was tested on the city of Naples (Italy), measuring the reduction in the heatwave impact/risks determined by the selected climate-proof solutions. The test results show the effectiveness of the climate-proof solutions applied to the built environment through an increase in climate resilience. The framework provides support for planning climatic resilience design strategies at the building scale. It could be applied in future local climate adaptation plans or as a knowledge resource to achieve resilient built environments.